HASIL BELAJAR MATEMATIKA PADA KURIKULUM MERDEKA - Anggraini, Daz Vholasky (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2024)
This research aims to analyze mathematics learning outcomes in the Independent Curriculum at the Elementary School (SD) and Junior High School (SMP) levels. The Merdeka Curriculum implemented in Indonesia emphasizes learning flexibility, giving schools and teachers the freedom to develop materials according to students' needs. The research method used is a literature review by collecting articles related to mathematics learning outcomes in the independent curriculum. There are 8 articles which are the main reference in this preparation. The research results show that the application of the Merdeka Curriculum in mathematics subjects has a positive impact on student learning outcomes. At the elementary level, student learning outcomes with semester average scores in the Merdeka curriculum are better than in the 2013 curriculum. Not only that, critical reasoning abilities and problem solving abilities also emerge. Meanwhile, at the junior high school level, the use of PPT, learning videos, developing LKPD, and learning models can support students' learning outcomes and mathematical abilities.